2016
DOI: 10.1071/mf14216
|View full text |Cite
|
Sign up to set email alerts
|

The hypoxia that developed in a microtidal estuary following an extreme storm produced dramatic changes in the benthos

Abstract: Runoff from an extreme storm on 22 March 2010 led, during the next 3 months, to the formation of a pronounced halocline and underlying hypoxia in the upper reaches of the microtidal Swan–Canning Estuary. Benthic macroinvertebrates were sampled between January 2010 and October 2011 at five sites along 10km of this region. By mid-April, the number of species, total density, Simpson’s evenness index and taxonomic distinctness had declined markedly, crustaceans had disappeared and the densities of annelids and mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 68 publications
0
31
1
Order By: Relevance
“…Thus, only relatively mobile or hypoxia tolerant animals were ever sampled in this study. This differs from the results of Tweedley et al (2016) that showed a shift in the community from hypoxia sensitive to hypoxia tolerant species, i.e., a loss of crustaceans and relative increase of annelids, after storm-induced hypoxia.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Thus, only relatively mobile or hypoxia tolerant animals were ever sampled in this study. This differs from the results of Tweedley et al (2016) that showed a shift in the community from hypoxia sensitive to hypoxia tolerant species, i.e., a loss of crustaceans and relative increase of annelids, after storm-induced hypoxia.…”
Section: Discussioncontrasting
confidence: 99%
“…Decomposition of algae further depresses dissolved oxygen, eventually resulting in hypoxia/anoxia and the development of toxic hydrogen sulphide and other stressors, e.g., ammonia (Valiela et al, 1997; Berezina, 2008). Sustained hypoxia or anoxia can have a catastrophic effect on the local faunal community with animals that are incapable of emigrating being at greatest risk (Ekau et al, 2010; Lyons et al, 2014; Tweedley et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, declining rainfall and river flows have reduced the frequency and scale of major flushing events (Silberstein et al ), encouraging increased water retention times and water column stratification (Hallett et al ). Hypoxia (i.e., dissolved O concentrations of <2 mgL −1 ) and harmful algal blooms are commonly associated with stratification events (Huang et al ) and are significant stressors of the system's ecology (Hallett, Valesini, Clarke et al ; Tweedley, Hallett et al ), periodically resulting in fish kills (Place et al ; Adolf et al ).…”
Section: Regional Context: Estuaries Of Southwestern Australiamentioning
confidence: 99%
“…These periods of bottom‐water hypoxia were typically associated with water column stratification following freshwater flows and were particularly marked in the upper parts of the estuary and in deeper holes. Such hypoxia, which occurs as O is consumed during the microbial decomposition of organic matter, has long been an issue in the upper estuary, where stratification is more prevalent and the sediments are rich in nutrients and organic matter (Douglas et al ; Kurup and Hamilton ; Tweedley, Hallett et al ).…”
Section: Key Outcomes From Fci Monitoring and Reportingmentioning
confidence: 99%